The genetic algorithm applied as a modelling tool to predict the fold of small proteins with different topologies - Dandekar, Thomas (Journal of molecular modeling, 1996)
The genetic algorithm exploits the principles of natural evolution. Solution trials are evolved by mutation, recombination and selection until they achieve near optimal solutions [1].
Gesehen am 08.08.2024